Super‐Resolution Fluorescence Microscopy Methods for Assessing Mouse Biology. Issue 8 (26th August 2021) - Valli, Jessica; Sanderson, Jeremy
Abstract: Super‐resolution (diffraction unlimited) microscopy was developed 15 years ago; the developers were awarded the Nobel Prize in Chemistry in recognition of their work in 2014. Super‐resolution microscopy is increasingly being applied to diverse scientific fields, from single molecules to cell organelles, viruses, bacteria, plants, and animals, especially the mammalian model organism Mus musculus . In this review, we explain how super‐resolution microscopy, along with fluorescence microscopy from which it grew, has aided the renaissance of the light microscope. We cover experiment planning and specimen preparation and explain structured illumination microscopy, super‐resolution radial fluctuations, stimulated emission depletion microscopy, single‐molecule localization microscopy, and super‐resolution imaging by pixel reassignment. The final section of this review discusses the strengths and weaknesses of each super‐resolution technique and how to choose the best approach for your research. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC.